An Enteropathy-like Indolent NK-Cell Proliferation Presenting in the Female Genital Tract. (April 2020) - Krishnan, Rahul; Ring, Kari; Williams, Eli; Portell, Craig; Jaffe, Elaine S.; Gru, Alejandro A.
Abstract : Natural killer (NK) cell enteropathy is a lymphoproliferative disorder, initially described by Mansoor and colleagues, that presents in the gastrointestinal tract, and is often mistaken for extranodal NK/T-cell lymphoma on first assessment. This population of cells in this process have an NK-cell phenotype (CD3, CD56, CD2, CD7), lacks evidence of Epstein-Barr virus infection, has germline rearrangement of the T-cell receptor, and a very indolent clinical course. Indeed, many of such patients had been originally diagnosed as having an NK/T-cell lymphoma, and subsequently received chemotherapy. We report a unique case where an indolent lymphoproliferative disorder with features that resemble NK-cell enteropathy is encountered for the first time outside the gastrointestinal tract, specifically in the female genitourinary tract. We provide morphologic, immunophenotypic, and molecular documentation of such, in association with a completely indolent clinical behavior of this type of process.